2014
DOI: 10.4168/aair.2014.6.4.333
|View full text |Cite
|
Sign up to set email alerts
|

Gene - Gene Interactions AmongMCPGenes Polymorphisms in Asthma

Abstract: PurposeMonocyte chemoattractant proteins (MCPs) are important cytokines that involved in cellular activation and releasing of inflammatoy mediators by basophils and eosinophils in allergic disease. Some MCP gene variants implicate in asthma and monoclonal antibody for MCP-3 blocks allergic inflammations in the patients with asthma. Detection of interactions between gene and environment or between genes for complex disease such as asthma is important. We searched for an evidence of genetic effect of single nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…MCP-1 stimulated trafficking of ATX to vesicles (Fig. 4A) and it can be anticipated that polymorphisms in the MCP-1 gene (Lee and Park, 2014) might influence the in vivo response. Functional polymorphisms for P2X7 (Ghalali et al, 2014) and P2X4 (Gu et al, 2013) individuals (Gui et al, 2014) and studies of P2X7 and P2X4 might be of interest because they have been implicated in other sensitization events.…”
Section: Discussionmentioning
confidence: 99%
“…MCP-1 stimulated trafficking of ATX to vesicles (Fig. 4A) and it can be anticipated that polymorphisms in the MCP-1 gene (Lee and Park, 2014) might influence the in vivo response. Functional polymorphisms for P2X7 (Ghalali et al, 2014) and P2X4 (Gu et al, 2013) individuals (Gui et al, 2014) and studies of P2X7 and P2X4 might be of interest because they have been implicated in other sensitization events.…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies have given considerable attention to the idea that genetic polymorphism might contribute to the development of asthma and may possibly be one of the reasons for these difference. 49 50 51 Liu found that the genotype and allele frequencies of the 2 SNPs Rs2289276 and Rs2289278 in the TSLP were significantly different between Chinese Han asthma patients and the healthy controls. The C allele of rs2289278 showed a close association with the decrease in FEV1:FVC.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the MCP-1 -2518 G polymorphism was correlated with asthma severity, and their results were subsequently supported by Keszei et al (15) and Tolgyesi et al (16). In contrast, two studies reported a protective effect of allele MCP-1 -2518 G polymorphism in asthmatic children (17,18), and three studies showed no significant association between MCP-1 -2518 G polymorphism and asthma risk (13,14,19). Our meta-analysis provided a more precise estimation based on a larger sample size compared with the individual study.…”
Section: Discussionmentioning
confidence: 85%
“…Of these, 5 articles were excluded because 3 articles were irrelevant, 1 article lacked a case-control design, and 1 article focused on another MCP-1 SNP site. Eventually, we identified 8 case-control publications, including 1562 asthma patients and 1574 controls, to evaluate the association of MCP-1 -2518 A>G polymorphism with asthma susceptibility (1219). There were three studies performed in Caucasian, three in Asian, and two in African populations.…”
Section: Resultsmentioning
confidence: 99%